Upconversion luminescence in Ho3+/Yb3+- and Tb3+/Yb3+-codoped fluorogermanate glass and glass ceramic - Gouveia-Neto, A. S.; Bueno, L. A.; Afonso, A. C. M.; Nascimento, J. F.; Costa, E. B.; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2008)
Energy-transfer excited upconversion luminescence in Ho3+/Yb3+- and Tb3+/Yb3+ -codoped PbGeO3-PbF2-CdF2 glass and glass-ceramic under infrared excitation is investigated. In Ho3+/Yb3+-codoped samples, green (545 nm), red (652 nm), and near-infrared (754 nm) upconversion emission corresponding to the S-5(2) (F-5(4)) -> I-5(8), F-5(5) -> I-5(8), and S-5(2)(F-5(4)) -> I-5(7) transitions, respectively, was observed. Blue (490 nm) emission assigned to the F-5(2,3) -> I-5(8) transition was also detected. In the Tb3+/Yb3+-codoped system, bright UV-visible emission around 384, 415, 438, 473-490, 545, 587, and 623 nm, identified as due to the D-5(3)((5)G(6)) -> F-7(J)(J = 6, 5, 4) and D-5(4) -> F-7(J)(J = 6, 5, 4, 3) transitions, was measured. The comparison of the upconversion process in glass ceramic and its glassy precursor revealed that the former samples present much higher upconversion efficiencies. The dependence of the upconversion emission upon pump power, and doping contents was also examined. The results indicated that successive energy-transfer between ytterbium and holmium ions and cooperative energy-transfer between ytterbium and terbium ions followed by excited-state absorption are the dominant upconversion excitation mechanisms herein involved. The viability of using the samples for three-dimensional solid-state color displays is also discussed. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: optical properties